Medium-to-long term macroeconomic effects of the COVID crisis: an investigation with RHOMOLO - Miguel Sanchez-Martinez; Martin Aarøe Christensen (European Commission, Joint Research Centre (JRC), 2022)
This paper provides an analysis of scenarios on the evolution of the EU GDP and aggregate consumption over the period 2020-2030, focusing on the role played by the COVID-19 shock. The gap between estimated precrisis trends and projected paths for three important variables are obtained using forecasting tools. These variables are the labour force participation rate, private investment, and public consumption, all of which have been significantly disrupted during and after the crisis. By using these projections as shocks in the RHOMOLO model, a number of interesting results on the potential impact of the crisis on future economic growth are obtained. A comparative analysis across EU Member States reveals important differences as regards the potential severity of the issue.
Keywords: 330; Coronavirus; Wirkungsanalyse; Modellierung; EU-Staaten